Packing Characteristics and Heat Transfer Performance of Non-Spherical Particles for Concentrated Solar Power Applications - Aidana Boribayeva; Xeniya Gvozdeva; Boris Golman (Energies, 2024)
Concentrated solar power (CSP) technology relies on thermal energy storage to extend operating hours, making the selection of heat storage media crucial for system efficiency. Bauxite powder, known for its availability and high-temperature stability, emerges as a potential alternative to conventional materials in CSP systems. This study employed the discrete element method to investigate the influence of particle shape on the packing and heat transfer characteristics of non-spherical particles. The research focused on assessing the impact of particle sphericity by comparing spherical particles with non-spherical shapes, including ellipsoids and cylinders, and exploring the effect of varying the aspect ratio (AR) of the cylindrical particles. Particle sphericity significantly influenced packing morphology, with the cylindrical particles exhibiting distinct structural patterns that were absent in the ellipsoidal particles, and strongly affected heat transfer, as observed in the average temperature variations within the packed bed over time. The cylinders with higher aspect ratios demonstrated enhanced heat transfer rates, driven by the increased contact area and coordination numbers, despite their predominant misalignment with the heat flux direction. These insights are valuable for optimizing thermal energy storage media in CSP systems.